Spatial variation in coral reef condition and reef fish assemblages along a proximity to Jakarta Bay, Indonesia - RIKOH MANOGAR SIRINGORINGO; DIETRIECH GEOFFREY BENGEN; I WAYAN NURJAYA; BEGINER SUBHAN; GIYANTO GIYANTO; RISANDI DWIRAMA PUTRA; MUHAMMAD ABRAR; NI WAYAN PURNAMA SARI; LUDI PARWADANI AJI (Society for Indonesian Biodiversity, 2025)
Abstract. Siringoringo RM, Bengen DG, Nurjaya IW, Subhan B, Giyanto, Putra RD, Abrar M, Sari NWP, Aji LP. 2025. Spatial variation in coral reef condition and reef fish assemblages along a proximity to Jakarta Bay, Indonesia. Biodiversitas 26: 5919-5930. The coral reef ecosystems of the Seribu Islands, Indonesia, exhibit complex ecological interactions between benthic assemblages and reef fish communities under the combined influence of local anthropogenic pressures and regional environmental stressors. This study examined benthic composition and reef fish functional structure across 14 sites along a spatial gradient from Jakarta Bay, Seribu Islands, to the outer islands. Benthic cover was assessed using the Underwater Photo Transect (UPT) method, and reef fish assemblages were quantified through Underwater Visual Census (UVC). Analyses revealed that distance from Jakarta Bay had a weak and inconsistent influence on benthic composition, with a low explanatory power for variations in hard coral cover (R²: 0.023, p: 0.6). In contrast, corallivorous fish abundance increased significantly with distance from the bay (R²: 0.30, p: 0.043), indicating a more pronounced spatial response among higher trophic groups. Cluster analyses identified three distinct ecological assemblages aligned with the nearshore-offshore gradient, reflecting subtle yet detectable shifts in community structure. These findings suggest that while benthic recovery remains constrained by persistent sedimentation and nutrient enrichment, reef fish assemblages particularly corallivores retain spatial sensitivity to urban influence. The emerging ecological differentiation across the archipelago underscores that the Seribu Islands function as a transitional system shaped by both urban proximity and broader ecological processes. Effective management should therefore integrate local mitigation of land-based stressors with broader seascape-scale strategies to enhance reef resilience in urban-influenced marine ecosystems.